Effect of Biochar on Vermicompost Production: Chemical, Biochemical, and Biological Properties - Antileo Mellado, Silvia (2024)
Farm and industrial residues must be adequately managed to avoid negative environmentalimplications. In this study, our objective was to evaluate (i) the impact of the co-production ofvermicompost using grape bagasse and biochar (BC) on the yield and biochemical, chemical, andbiological properties of vermicompost; (ii) the effect of BC on earthworms (Eisenia fetida Sav.). Thevermicompost was co-produced over 5 months (n = 4 per treatment) using (i) grape bagasse asthe substrate, (ii) earthworms (Eisenia fetida Sav.), and (iii) three BCs (eucalyptus sawdust BC, pigmanure BC, and carbonaceous material from poultry litter CM) at 2% (w/w). A control without BCwas included. The chemical, microbiological (activity and respiration), enzymatic properties, andenzymatic indices were characterized. After the incubation period, vermicompost yield increasedwith the application of the three BCs (25% on average). The number of adult earthworms was notaffected by any of the BCs. Compared to treatments without BC, those with pig manure BC andeucalyptus BC resulted in maintained or significantly decreased enzymatic activity, indicating thatthe vermicompost was at an advanced stage of maturity. Eucalyptus BC significantly enriched the Ccontent of the vermicompost by 4.3%, maintaining respiration rates at 18% lower than the treatmentwithout BC. Additionally, pig manure BC generated the lowest respiration rate in the vermicompost(20% lower). We conclude that BC has a positive influence on the vermicompost process, stabilizingorganic matter (especially pig manure BC) and improving the potential of vermicompost to store C(when high-C-content BCs are applied).